Association of the oral microbiome with the progression of impaired fasting glucose in a Chinese elderly population. Issue 1 (1st January 2019) - Wang, Rui-Rui; Xu, Yue-Song; Ji, Meng-Meng; Zhang, Li; Li, Dong; Lang, Qing; Zhang, Lei; Ji, Guang; Liu, Bao-Cheng
ABSTRACT: Objective: The oral microbiota is associated with the risk of type 2 diabetes (T2D), but the relationship between the oral microbiota and disease progression in the elderly population remains to be determined. Design: In our study, we recruited 150 elderly Chinese residents and divided them into three groups according to their fasting glucose (FG) level: normal (N), high (H), and very high (VH). Their biochemical indexes were analyzed using blood samples. Saliva samples were collected and the oral microbiome was profiled by high-throughput sequencing of the V3-V4 area of the 16S rRNA gene. Result: Our results revealed that the VH group showed deterioration of the metabolic phenotype and dysbiosis of the oral microbiota simultaneously when compared to the other two groups. Furthermore, potential disease-associated bacterial genera including Leptotrichia, Staphylococcus, Catonella, and Bulleidia were significantly enriched in the VH group. Conclusions: These results suggest that dysbiosis of the oral microbiota may be a typical feature of hyperglycemia and might also contribute to disease aggravation in the progression of hyperglycemias.